Thermography Diagnosis of Medial Patellar Ligament Rupture in a Horse - Dogan, Elif; Deniz, Omer; Dellalbasi, Ayse Basak (Kafkas University, 2023)
In this report, thermography was evaluated as a portable diagnostic tool in addition to ultrasonography, which is frequently used in the diagnosis of medial patellar ligament tears in horses. Thermography revealed that the medial patellar ligament has difficulty absorbing quadriceps forces and that the cranial surface of the stifle joint shows elevated temperatures at rest. At the end of training, load sharing occurred between the cranial and caudal surfaces of the joint and the quadriceps muscle. Temperature changes captured by thermography may indicate the severity of the injury and help clinicians suspect ligament tears even without access to ultrasonography.
Keywords: medial patellar ligament rupture; Veterinary medicine; SF600-1100; horse; thermography; 2. Zero hunger